The effect of Workplace Fun on Work Engagement by Psychological Capital as a Mediating Variabel - Sakinah, Ulfi; Trinanda, okki (Human Resource Management Studies, 2023)
This study aims to analyze: (1) The effect of Workplace Fun on Work Engagement (2) The effect of Workplace Fun on Psychological Capital (3) The effect of Psychological Capital on Work Engagement (4) The effect of Workplace Fun on Work Engagement through Psychological Capital. This research is a causal research. The population in this study were all employees of the UPT Puskesmas Lima Kaum 1 Tanah Datar Regency, totaling 42 people. While the number of samples used in this study was determined using total sampling so that the sample is the same as the population, which is 42 people. The analysis technique used is SmartPLS 4 software. The results of this study indicate that: (1) Workplace Fun has a positive and significant effect on Work Engagement for employees of UPT Puskesmas Lima Kaum 1 Tanah Datar Regency. (2) Workplace Fun has a positive and significant effect on Psychological Capital for employees of UPT Puskesmas Lima Kaum 1 Tanah Datar Regency. (3) Psychological Capital has a positive and significant effect on Work Engagement for employees of UPT Puskesmas Lima Kaum 1 Tanah Datar Regency. (4) Workplace Fun has a positive and significant effect on Work Engagement with Psychological Capital as a mediating variable for employees of UPT Puskesmas Lima Kaum 1 Tanah Datar Regency.